Lavra in the desert: Nuno Guimarães’ poetics - Erthal, Aline Duque (2015)
The politic answer to modern reading and experiencing of the real was given in various ways in Portuguese poetry post-1960. Contemporaneous eyes are focusing with increasing attention those writings, but one name remains undeservedly obscure: Nuno Guimarães. Despite the short life and production, the poet erected a work that intersects the main lines of reflection of the 60’s and trends that would be developed in the 70’s; at the same time, he exhibits a voice which is independent and mature enough to deserve an ethical and poetic place of interest in the Portuguese literature panorama.